REVIEW OF THE COURSEBOOK OF JAPAN FOUNDATION «MARUGOTO. JAPANESE LANGUAGE AND CULTURE» - Р.Н., Кaжaтовa; Е.А., Ахaпов (Journal of Oriental Studies, 2019)
The article is focused on the standard for teaching Japanese language and on the coursebook “Maru- goto. Japanese language and culture” based on the standard. Moreover, a brief overview of the activities Japan Foundation in the dissemination of the Japanese language in the world. This article analyzes the annual report of the teaching Japanese language worldwide and describes main features of the Japanese language standard. The purpose of the article is to examine the standard of teaching Japanese language and the coursebook “Marugoto. Japanese language and culture” as an example of teaching the Kazakh language for foreigners. To highlight the importance of a certain language learning system and training materials that is suitable for this system by determining the features of the standard of teaching Japanese and the coursebook based on the standard. Key words: Japan Foundation, Japanese language, JF Standard for Japanese-Language, Marugoto.